Effect of reactor pressure on optical and electrical properties of InN films grown by high-pressure chemical vapor deposition - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2015)
The influences of reactor pressure on the stoichiometry, free carrier concentration, IR and Hall determined mobility, effective optical band edge, and optical phonon modes of HPCVD grown InN films have been analysed and are reported. The In 3d, and N 1s XPS spectra results revealed In-N and N-In bonding states as well as small concentrations of In-O and N-O bonds, respectively in all samples. InN layers grown at 1 bar were found to contain metallic indium, suggesting that the incorporation of nitrogen into the InN crystal structure was not efficient. The free carrier concentrations, as determined by Hall measurements, were found to decrease with increasing reactor pressure from 1.61x10(21) to 8.87x10(19) cm(-3) and the room-temperature Hall mobility increased with reactor pressure from 21.01 to 155.18 cm(2)/Vs at 1 and 15 bar reactor pressures, respectively. IR reflectance spectra of all three (1, 8, and 15 bar) InN samples were modelled assuming two distinct layers of InN, having different free carrier concentration, IR mobility, and effective dielectric function values, related to a nucleation/interfacial region at the InN/sapphire, followed by a bulk InN layer. The effective optical band gap has been found to decrease from 1.19 to 0.95 eV with increasing reactor pressure. Improvement of the local structural quality with increasing reactor pressure has been further confirmed by Raman spectroscopy measurements. (c) 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: indium nitride; high-pressure CVD; superatmospheric; MOCVD; XPS; Hall measurements; FTIR